Removal of bisphenol S from aqueous solution using activated carbon derived from rambutan peel via microwave irradiation technique - Azrina Aziz; Mohamad Firdaus Mohamad Yusop; Mohd Azmier Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2022)
Bisphenol S (BPS) was introduced to replace Bisphenol A (BPA) in plastic production. Unfortunately, recent studies have shown that BPS is toxic. This study explores the conversion of rambutan peel into rambutan peel-based activated carbon (RPAC) via the economic route of single-stage microwave irradiation technique at radiation power and radiation time of 440 W and 6 min, respectively, under CO2 gasification. The resulted RPAC posed BET surface area of 402.68 m2/g, mesopores surface area of 332.98 m2/g, total pore volume of 0.23 cm3/g, and average pore diameter of 2.26 nm, which lies in the mesopores region. The surface of RPAC was filled with various functional groups such as methylene, aliphatic fluoro, phenol, nitro, and alkyl compounds. Adsorption of BPS onto RPAC achieved equilibrium faster at lower BPS initial concentration as compared to the higher ones. Isotherm study found that the Langmuir model suits this adsorption process the best with a maximum monolayer adsorption capacity of 27.89 mg/g whereas the kinetic study showed that pseudo-second order (PSO) represented the kinetic data the best. Intraparticle diffusion plots suggested that the adsorption process consisted of three regions and each region was controlled by a different type of diffusion mechanism. Boyd plot confirmed that film diffusion was responsible for the slowest step in the adsorption process whilst thermodynamic parameters disclosed that adsorption of BPS onto RPAC was spontaneous, exothermic, governed by physisorption, and the randomness of the adsorption process was found to reduce at the solid-liquid interface.